Relationship Between Early Mobilization and The Wound Healing Process of Post Sectio Caesaria in The Maternity Room of RSUD Kabupaten Kediri - Sripina Ulandari; Eva Nur Azizah; Ratna Feti Wulandari (Journal of Ners and Midwifery, 2022)
Sectio caesarea is an artificial labor where the fetus was born through an incision in the abdominal wall and the uterus’ wall on the condition of the uterus intact and fetal weight above 500 grams. Labor by Sectio caesarea  causes sores and pain. The presence of wounds and pain causes the mother to be lazy or afraid to mobilize. Early mobilization is a rehabilitative action that is carried out after the patient is awake from anesthesia and after surgery. This study aims to analyze the relationship between early post-sectio caesarea mobilization and the wound healing process of post operative sectio cesaria.  This study used a cross sectional method and the sample was collected as many as 40 respondents using simple random sampling technique. The research data was taken using a questionnaire and then analyzed using the contingency coefficient test. The results showed that almost all of them as many as 35 respondents (87.0%) did early mobilization. The wound healing process of Sectio Caesarea was almost entirely in the good category, namely 35 respondents (87.0%). Contingency coefficient test results obtained = 5%= 0.05, p<α Positive relationship, postpartum mothers often do early mobilization, the better the wound healing. C = 0.611 means a strong relationship level. From the results of these studies, it is necessary to increase the knowledge of post partum mothers about the factors that accelerate the wound healing process of post sectio Caesarea